2016
DOI: 10.1002/ejhf.675
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and prognostic implications of the negative diastolic pulmonary pressure gradient in patients with pulmonary hypertension due to left heart disease

Abstract: AimsThe diastolic pulmonary pressure gradient (DPG) has recently been introduced as a specific marker of combined pre-capillary pulmonary hypertension (Cpc-PH) in left heart disease (LHD). However, its diagnostic and prognostic superiority compared with traditional haemodynamic indices has been challenged lately. Current recommendations explicitly denote that in the normal heart, DPG values are greater than zero, with DPG ≥7 mmHg indicating Cpc-PH. However, clinicians are perplexed by the frequent observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…Importantly, CpcPH and IpcPH patients exhibited a clearly distinct exercise response, indirectly justifying the practice of preferring the PVR criterion. Interestingly, we found a high proportion of patients with negative DPG (as evident from the data in Table ), which is in line with the findings from patients with mitral stenosis and PH due to HF with reduced or preserved ejection fraction as reported by Nagy et al . They showed that negative DPG values were associated with the presence of large V waves in patients with PVR < 3 WU.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, CpcPH and IpcPH patients exhibited a clearly distinct exercise response, indirectly justifying the practice of preferring the PVR criterion. Interestingly, we found a high proportion of patients with negative DPG (as evident from the data in Table ), which is in line with the findings from patients with mitral stenosis and PH due to HF with reduced or preserved ejection fraction as reported by Nagy et al . They showed that negative DPG values were associated with the presence of large V waves in patients with PVR < 3 WU.…”
Section: Discussionsupporting
confidence: 92%
“…They showed that negative DPG values were associated with the presence of large V waves in patients with PVR < 3 WU. In our study, as in the study by Nagy et al ., mPAWP was obtained from the entire cardiac cycle including V waves. This probably has resulted in higher mPAWP values compared to a practice of not including V waves, which in turn has resulted in lower DPG, TPG, and PVR values.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary vascular resistance differentiated patients at high and low risk. In contrast, no difference in survival was found based on the diastolic pressure gradient, consistently with previous data regarding this parameter …”
Section: Prognostic Variablessupporting
confidence: 91%
“…At present, an almost equal number of studies have confirmed [41][42][43] or refuted [44][45][46] the prognostic relevance of DPG. These discrepancies are explained by the fact that the DPG represents a small number, is exposed to instability, as shown in studies where high DPGs were sometimes found in patients with a normal PVR 44 or where DPG was reported as negative in a proportion of patients, 47 conditions which are both physiologically impossible. TPG or PVR have to increase in proportion of the DPG, 7 while reported negative DPG values may be because of improper incorporation of V waves in the reading of PAWP tracings or simply because of a lack of precision of the measurement.…”
Section: The Diastolic Pulmonary Pressure Gradientmentioning
confidence: 99%